2018
DOI: 10.21815/jde.018.103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Interprofessional Oral Health Assessment Activity in Advanced Practice Nursing Education

Abstract: The curriculum for nurse practitioner (NP) students often overlooks the assessment of the oral cavity. In recognition of this, the HEENT (head, eyes, ears, nose, and throat) assessment was expanded to HEENOT (head, ears, eyes, nose, oral, and throat) through integration of an interprofessional educational (IPE) activity developed for University of Colorado NP and dental students. The aim of this study was to assess NP students’ perceptions of an IPE activity in which dental faculty and students taught NP stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…While challenges remain in coordinating curricula across disciplines to facilitate students' involvement in IPE initiatives, providing nursing students with opportunities to include oral health assessments in their assessment of overall body function would significantly improve the health outcomes of older people [32,58]. IPE models have been implemented successfully in many graduate nursing programs in addition to undergraduate nursing programs [46,[59][60][61][62][63]. The "Smile for Life-National Oral Health Curriculum" has been popular with graduate nursing students [17,59,[62][63][64].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…While challenges remain in coordinating curricula across disciplines to facilitate students' involvement in IPE initiatives, providing nursing students with opportunities to include oral health assessments in their assessment of overall body function would significantly improve the health outcomes of older people [32,58]. IPE models have been implemented successfully in many graduate nursing programs in addition to undergraduate nursing programs [46,[59][60][61][62][63]. The "Smile for Life-National Oral Health Curriculum" has been popular with graduate nursing students [17,59,[62][63][64].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In addition to specific ohr-interRAI training programs, the attention for oral health in the training of healthcare students needs to be increased as well. Current curricula of nursing students often cover the topic insufficiently, but it was repeatedly shown that particularly inter-professional education is suited to improve oral health-related knowledge, competence, and confidence among nursing students [54][55][56][57].…”
Section: Interpretation Of the Results And Future Prospectsmentioning
confidence: 99%
“…The students' confidence in oral assessment performance improved in all assessment categories after the educational programmes; therefore, these programmes might be effective in facilitating performance improvement. A previous study of an interprofessional oral health assessment educational programme, in which dental faculty and students taught nursing students, reported that the students' confidence in performing oral assessments improved after the programmes (Estes et al, ). On the other hand, the educational programmes for oral assessment offered for nurses were not effective in improving the nurses' confidence (Haresaku et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There were also some studies regarding the effects of interprofessional education that specialized in improving nurses' oral assessment performance (Andersson et al, 2002;Aoki et al, 2018;Chalmers et al, 2005;Coan, Wijesuriya, & Seibert, 2019;Eilers et al, 1988;Haresaku et al, 2018b;Munoz, Touger-Decker, Byham-Gray, & Maillet, 2009;Tsukada et al, 2017). In addition, a previous study of nursing students reported that their confidence in oral assessment performance was improved after the oral assessment interprofessional education programmes (Estes et al, 2018). However, there were no studies regarding the effect of interprofessional education programmes that specialized in improving nursing students' abilities to perform oral assessments and their selforal assessment performance.…”
Section: Introductionmentioning
confidence: 99%